2005
DOI: 10.1021/ja0504690
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Hydrogen Evolution:  MoS2Nanoparticles as Catalyst for Hydrogen Evolution

Abstract: The electrochemical hydrogen evolution reaction is catalyzed most effectively by the Pt group metals. As H2 is considered as a future energy carrier, the need for these catalysts will increase and alternatives to the scarce and expensive Pt group catalysts will be needed. We analyze the ability of different metal surfaces and of the enzymes nitrogenase and hydrogenase to catalyze the hydrogen evolution reaction and find a necessary criterion for high catalytic activity. The necessary criterion is that the bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

73
2,936
2
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 3,641 publications
(3,089 citation statements)
references
References 24 publications
73
2,936
2
12
Order By: Relevance
“…In 2005, inspired by hydrogen‐producing enzymes, a density functional theory (DFT) calculation predicted that the edge sites of MoS 2 would be active for the HER, which could be an alternative to the Pt group in acidic conditions 103. In 2007, it was experimentally confirmed that the edge sites of MoS 2 are clearly the active sites for the HER, which can reach −10 mA cm −2 at an overpotential of 200 mV 104, 105.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%
“…In 2005, inspired by hydrogen‐producing enzymes, a density functional theory (DFT) calculation predicted that the edge sites of MoS 2 would be active for the HER, which could be an alternative to the Pt group in acidic conditions 103. In 2007, it was experimentally confirmed that the edge sites of MoS 2 are clearly the active sites for the HER, which can reach −10 mA cm −2 at an overpotential of 200 mV 104, 105.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%
“…The Δ E ZPE can be obtained via vibrational frequency calculation. The Δ S H can be regarded as ΔSnormalH12SnormalH20 due to the fact that the vibrational entropy in the adsorbed state is small according to previous studies 28, 40. The optimal value for HER is Δ G H = 0, which means that the smaller values of |Δ G H |, the better HER performance of materials.…”
Section: Methodsmentioning
confidence: 94%
“…With high cost, it is less competitive in practical application. MoS 2 becomes an alternative of active HER electrocatalysts135, 150 since the first report by Hinnemann et al in 2005 151. Both experimental and computational results identified that the sulfur edges of MoS 2 are the active sites for HER, which are structurally distinct from the inactive bulk material.…”
Section: Electrocatalytic Water Splittingmentioning
confidence: 99%